Do Optional Deductibles Reduce the Number of Doctor Visits? – Empirical Evidence with German Data - Hendrik Schmitz (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
Deductibles in health insurance are often regarded as a means to contain health care costs when individuals exhibit moral hazard. However, in the absence of moral hazard, voluntarily chosen deductibles may instead lead to self-selection into different insurance contracts. We use a set of new variables in the German Socioeconomic Panel for the years 2002, 2004, and 2006 that measure individual health more accurately and include risk-attitudes towards health in order to determine the price elasticity of demand for health care. A latent class approach that takes into account the panel structure of the data reveals that the effect of deductibles on the number of doctor visits is negligible. Private add-on insurance increases the number of doctor visits. However, altogether the effects of the insurance state on the demand for doctor visits are small in magnitude.
Keywords: I11; I18; G22; 330; Health insurance; deductibles; add-on insurance; count data; latent class panel model; Ärzte; Patienten; Nachfrage; Gesetzliche Krankenversicherung; Selbstbeteiligung (Versicherung); Private Krankenversicherung; Konsumentenverhalten; Schätzung; Deutschland